PERBANDINGAN PROSES PENGANGKATAN ANAK YANG TIDAK DIKETAHUI ASAL USULNYA (NASABNYA) DITINJAU DARI PERSPEKTIF FIQIH ISLAM DAN HUKUM POSITIF INDONESIA - SUCI MULANI (PREMISE LAW JURNAL, 2016)
Concept of adoption is of unknown origin according to the perspective of the Islamic Fiqh, basically there was never any concept of adoption as set out in the Child Protection Act and Government Regulation of Adoption, Islamic Fiqh justify Hadhanah (childcare) Istilhaq concept, while according to the perspective of the Child Protection Act and KHI and Government Regulation No. 54 of 2007 on the Implementation of Child Adoption, prospective adoptive parents apply for adoption who have met the requirements to court to obtain a court warrant. Adoption should be confirmed by a court decision. Equation concept of adoption according to Islamic jurisprudence is positive law requires the same religion for parents and adopted children, considers that the adoption can not decide on a blood relationship between the adopted child with his biological parents, and also require the adoptive parents not to hide the identity of biological parents of the child. While the difference lies in the position of adopted children, about the manner of adoption, and of inheritance, the adoption of Islamic law does not give rise to inherit inheritance relationship between them is in the positive law explained that the adopted child is entitled to inheritance. Keywords: Child Adoption, Child Care, Islamic Fiqh/Jurisprudence, Positive Law.